2000
DOI: 10.1523/jneurosci.20-23-08717.2000
|View full text |Cite
|
Sign up to set email alerts
|

Presenilin-1 P264L Knock-In Mutation: Differential Effects on Aβ Production, Amyloid Deposition, and Neuronal Vulnerability

Abstract: The pathogenic mechanism linking presenilin-1 (PS-1) gene mutations to familial Alzheimer's disease (FAD) is uncertain, but has been proposed to include increased neuronal sensitivity to degeneration and enhanced amyloidogenic processing of the ␤-amyloid precursor protein (APP). We investigated this issue by using gene targeting with the Cre-lox system to introduce an FAD-linked P264L mutation into the endogenous mouse PS-1 gene, an approach that maintains normal regulatory controls over expression. Primary co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
105
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(122 citation statements)
references
References 79 publications
17
105
0
Order By: Relevance
“…Several interesting findings emerged: (i) similar to our previous analysis of endogenous A␤ (35), reduction of 50% PS1 dosage resulted in a significant decrease in both A␤40 and A␤42 without altering the ratio of A␤42/A␤40 (compare ϩ/ϩ with ϩ/Ϫ; Fig. 3, C-E); (ii) consistent with the A␤ data obtained from PS1 A264L knock-in mice (23), expression of the PS1 M146V FAD mutation was accompanied by a simultaneous reduction of A␤40 and increase in A␤42 (compare ϩ/ϩ with M146V/ϩ; Fig. 3, C and D); (iii) removal of the remaining wild-type PS1 from the APP/PS1 M146V/ϩ mice led to a further reduction of A␤40 without significantly affecting A␤42 (compare M146V/Ϫ with M146V/ϩ; Fig.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Several interesting findings emerged: (i) similar to our previous analysis of endogenous A␤ (35), reduction of 50% PS1 dosage resulted in a significant decrease in both A␤40 and A␤42 without altering the ratio of A␤42/A␤40 (compare ϩ/ϩ with ϩ/Ϫ; Fig. 3, C-E); (ii) consistent with the A␤ data obtained from PS1 A264L knock-in mice (23), expression of the PS1 M146V FAD mutation was accompanied by a simultaneous reduction of A␤40 and increase in A␤42 (compare ϩ/ϩ with M146V/ϩ; Fig. 3, C and D); (iii) removal of the remaining wild-type PS1 from the APP/PS1 M146V/ϩ mice led to a further reduction of A␤40 without significantly affecting A␤42 (compare M146V/Ϫ with M146V/ϩ; Fig.…”
Section: Resultssupporting
confidence: 85%
“…This can result from elevated production of A␤42, a reduction of A␤40, or both combined. Indeed, several publications indicate that increase in A␤42 is at the expense of reduced A␤40 (23,24), suggesting that the apparent gain of A␤42 could be secondary to partial loss of cleavage at A␤40 or other ␥-secretase sites. Furthermore, because the wild-type PS1 is present in all reported studies, whether the observed changes in A␤42/A␤40 ratio are due to intrinsic properties of the mutant protein or the interactions between the wild type and the mutant PS1 has not been explored.…”
mentioning
confidence: 99%
“…Perhaps more surprisingly, numerous mutations in PS1 (e.g., N135D, L166P, M233T, P264L, G384A, and C410Y) and PS2 (e.g., T122P, N141I, M239V, and M239I) can cause significant reductions in the production of A␤40, often despite a concomitant increase in the production of A␤42 (12)(13)(14)(16)(17)(18)(19). The differential effect of PS mutations on alternative cleavage positions in the APP transmembrane domain seems not to represent a simple shift in substrate preference or specificity, because the degree of elevation in A␤42 levels with individual mutations does not correlate with the degree of depression in A␤40 or AICD levels (e.g., ref.…”
Section: Fad-linked Ps Mutations Impairmentioning
confidence: 99%
“…More than 100 mutations have been identified in PS1 and PS2, and they spread throughout the entire molecules. These mutations are known to alter the ␥-secretase activity, often resulting in increased A␤42 production at the expense of A␤40 (2,3). Through similar mechanisms defined as regulated intramembrane proteolysis (4), PS are required for processing and signaling of Notch (5), and this pathway likely contributes to various PS developmental activities (6).…”
Section: Ammalian Presenilins (Ps) Consists Of Two Homologous Pro-mentioning
confidence: 99%